2012
DOI: 10.1039/c2jm32138f
|View full text |Cite
|
Sign up to set email alerts
|

ZnV2O4–CMK nanocomposite as an anode material for rechargeable lithium-ion batteries

Abstract: In the present work, the nanocomposite ZnV 2 O 4 -CMK was synthesized for the first time by using a low temperature carbothermal reduction route and was then characterized by means of X-ray diffraction (XRD), thermogravimetric analysis (TG), N 2 adsorption-desorption, scanning and transmission electron microscopy (SEM/TEM). Furthermore, the nanocomposite was used for the first time as an anode material for Li-ion intercalation and exhibited a large reversible capacity, high rate performance and cycling stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 37 publications
5
39
1
Order By: Relevance
“…Therefore, the active process includes the phase transformation and the change of the reaction microenvironment, which will reach a stable value after some cycles. This active process was also observed in the previous literature [16]. Fig.…”
Section: Electrochemical Characterizationsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, the active process includes the phase transformation and the change of the reaction microenvironment, which will reach a stable value after some cycles. This active process was also observed in the previous literature [16]. Fig.…”
Section: Electrochemical Characterizationsupporting
confidence: 70%
“…The reversible capacity increases slowly in the about 20 anterior cycles, then stabilizes and remains at an almost constant level of 660 mAh g À1 . Compared to the previous studies, the ZnV 2 O 4 -CMK nanocomposites with 30e80 nm showed a reversible capacity of 424 mAh g À1 at initial cycle and an increasing capacity of 575 mAh g À1 at 200 th cycle [16]. The as prepared ZnV 2 O 4 nanoparticles with higher reversible capacity are approximately due to smaller particle size (~20 nm) to enhance the reaction kinetics.…”
Section: Electrochemical Characterizationmentioning
confidence: 90%
“…This peculiarly structured ZnV 2 O 4 electrode exhibited almost stable cycling performance to maintain a capacity of 524 mAh g À1 over 50 cycles. Zeng et al synthesized nanocomposite ZnV 2 O 4 -CMK by a low temperature carbothermal reduction route [23] and a reversible capacity of 575 mAh g À1 was maintained even after 200 cycles at a current density of 0.1 A g À1 . Sun et al reported a shapecontrolled monoclinic micro/nanostructured ZnV 2 O 6 through a simple hydrothermal approach [24].…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39] The mesochannel and large surface area of MC shortens the distance of Li-ion diffusion and its high conductivity is in favor to electron transmission. On the other hand, it has large pore volumes, which offer a better accommodation of the strain and volume changes during the charge-discharge process.…”
Section: Introductionmentioning
confidence: 99%